2017
DOI: 10.1563/aaid-joi-d-16-00212
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Length of the Anterior Loop of the Inferior Alveolar Nerve in Iranians

Abstract: The anterior loop of the inferior alveolar nerve is a sensitive anatomical feature that should be taken into account during installation of dental implants anterior to the mental foramen. This study was conducted to explore the controversy regarding prevalence and length. A total of 452 mandible quadrants of 234 patients (age: 50.1 ± 13.3 years, 113 males, 121 females) were studied using cone-beam computerized tomography. After reconstructing axial, frontal, and sagittal slices, the region between the most ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…The mean length of the loop is 2.79 mm in our study which is a middle value in literature where the mean length varies from 0.4 to 6 mm . ‐ …”
Section: Discussionmentioning
confidence: 54%
“…The mean length of the loop is 2.79 mm in our study which is a middle value in literature where the mean length varies from 0.4 to 6 mm . ‐ …”
Section: Discussionmentioning
confidence: 54%
“…Considering these findings, it is important to consider a minimum safe distance to the AL, which may vary widely in function of the different studies carried out: 2 mm, 4 mm, or 6 mm. [192021222324] In practical terms, we emphasize the importance of a case by case evaluation and no specific measurements for a safety distance. Individual, gender, age, race, assessing technique used, and degree of alveolar bone atrophy largely influence the different anatomical variations.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AL in Brazilians varied from 10.2% to 41.6%. [10][11][12] In Iran, there is a discrepancy in the prevalence of anterior loop as well, ranging from 32.8% to 84% in different studies. 7, 11,13, 14 Apostolakis et al, 15 reported that the prevalence of AL was 48% within the Greeks with a mean length of 0.89mm (range 0mmm-5.7mm).…”
Section: Palabras Clavementioning
confidence: 99%